2019
DOI: 10.30534/ijatcse/2019/116852019
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone-Based Skin Disease Classification Using MobileNet CNN

Abstract: The MobileNet model was used by applying transfer learning on the 7 skin diseases to create a skin disease classification system on Android application. The proponents gathered a total of 3,406 images and it is considered as imbalanced dataset because of the unequal number of images on its classes. Using different sampling method and preprocessing of input data was explored to further improved the accuracy of the MobileNet. Using under-sampling method and the default preprocessing of input data achieved an 84.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 18 publications
0
35
0
3
Order By: Relevance
“…The implemented model was based on CNN for the recognition of a group of oral lesions, using the Mobilenet V2 network pre-trained with ImageNet, which is characterized by being a large database with several categories including plants, flowers, animals, objects, among others, with excellent results at the time of classification [11,12]. This is the reason why this model was considered to perform the learning transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implemented model was based on CNN for the recognition of a group of oral lesions, using the Mobilenet V2 network pre-trained with ImageNet, which is characterized by being a large database with several categories including plants, flowers, animals, objects, among others, with excellent results at the time of classification [11,12]. This is the reason why this model was considered to perform the learning transfer.…”
Section: Discussionmentioning
confidence: 99%
“…This is the reason why this model was considered to perform the learning transfer. Lesion recognition systems using learning transfer have been described in the literature with the AlexNet [11], VGGNet [13,14], and ResNet [12,[15][16][17][18] network models, whose performance is similar to the model used for this work.…”
Section: Discussionmentioning
confidence: 99%
“…The TensorFlow Object Detection API library comprises of object detection structures, such as Single Shot Detector (SSD), Faster Region-based Convolutional Neural Network (Faster R-CNN), etc. Feature extractors such as Inception, MobileNet [16] and Resnet play critical roles in the speed and accuracy trade-off of the framework. Even with the recent studies of various researchers, constructing convolutional networks from scratch requires a great volume of image datasets and a long period of training and testing time.…”
Section: B Tensorflow Object Detection Apimentioning
confidence: 99%
“…In selecting a pre-trained model, the performance, speed, and mean Average Precision (mAP) that define the accuracy of the detector were considered, as in [16] [18]. According to the analysis of Huang et al [15], the Faster R-CNN model with Inception V2 and SSD model with Inception V2 yields a mAP of 28 and 24, respectively, which requires a speed of at least 58 ms and 42 ms per image, respectively.…”
Section: Configuring the Pipelinementioning
confidence: 99%
“…This results in ten validations, with a total of 320 images, 40 images from each class. The performance of the networks is measured by calculating accuracy, precision, sensitivity, specificity, F1 score, and Mathews correlation coefficient (MCC) for all the seven macular deformities as well as normal cases from the confusion matrix [28]. From the results, it is observed that ResNet performs better than the other two CNNs as shown in Table 2.…”
Section: Development Of An Intelligent System For Dme Categorisationmentioning
confidence: 99%